2019
DOI: 10.3390/cancers12010050
|View full text |Cite
|
Sign up to set email alerts
|

Application of an Artificial Intelligence Algorithm to Prognostically Stratify Grade II Gliomas

Abstract: 1) Background: Recently, it has been shown that the extent of resection (EOR) and molecular classification of low-grade gliomas (LGGs) are endowed with prognostic significance. However, a prognostic stratification of patients able to give specific weight to the single parameters able to predict prognosis is still missing. Here, we adopt classic statistics and an artificial intelligence algorithm to define a multiparametric prognostic stratification of grade II glioma patients. (2) Methods: 241 adults who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 45 publications
1
20
1
Order By: Relevance
“…Numerous studies have recently demonstrated that the maximal safe extent of tumoral resection (EOR) is the first-line treatment resulting in better survival [ 21 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. In the last decade, the qualitative and subjective descriptions of EOR as “gross total resection”, “near total resection”, and “subtotal resection”, are being replaced by precise and objective estimation based on the volume of residual tumor according to the following formula: “EOR = preoperative tumor volume − postoperative tumor volume/preoperative tumor volume” [ 21 , 66 ].…”
Section: Role Of Surgerymentioning
confidence: 99%
“…Numerous studies have recently demonstrated that the maximal safe extent of tumoral resection (EOR) is the first-line treatment resulting in better survival [ 21 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. In the last decade, the qualitative and subjective descriptions of EOR as “gross total resection”, “near total resection”, and “subtotal resection”, are being replaced by precise and objective estimation based on the volume of residual tumor according to the following formula: “EOR = preoperative tumor volume − postoperative tumor volume/preoperative tumor volume” [ 21 , 66 ].…”
Section: Role Of Surgerymentioning
confidence: 99%
“…All histological samples were reviewed according to the 2016 World Health Organization (WHO) classification 21 . Molecular markers were evaluated as previously described 22 .…”
Section: Methodsmentioning
confidence: 99%
“…All histological samples were reviewed according to the 2016 World Health Organization (WHO) classification ( 9 ). Molecular markers were evaluated as previously described ( 13 ).…”
Section: Methodsmentioning
confidence: 99%